Responsible conduct of research - Shamoo, Adil E.; Resnik, David B. (Oxford : Oxford University Press, 2009)
A comprehensive introduction to the ethical issues at stake in the conduct of biomedical research, with extensive use of case examples. Its content parallels the recommendations of the Commission on Research Integrity, and deals with ethical issues in the use of animal and humans in research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medicine -- Research -- Moral and ethical aspects; Medical ethics; Bioethics; Human experimentation in medicine -- Moral and ethical aspects